Experimental study on Steel Fiber Reinforced Concrete and Reinforced Concrete elements under concentrated loads. (8th November 2021) - Trabucchi, Ivan; Tiberti, Giuseppe; Conforti, Antonio; Medeghini, Filippo; Plizzari, Giovanni A.
Graphical abstract: Highlights: From splitting to crushing collapse, by adopting SFRCs with adequate toughness. SFRC samples with limited toughness manage equilibrium with longer splitting crack. High FRC performance is useless when concrete crushing is governing. Fiber orientation & distribution strongly affect bearing capacity & failure mechanism. SFRC with shorter fibers can achieve a better crack control at crack-formation stage. Abstract: Concrete elements subjected to high compressive loads applied over a small contact area is a typical engineering problem. The partially loaded area leads to high compressive stresses underneath the loading zone, that can cause crushing failure, and tensile transverse stresses, which could provoke splitting failure. Rebars are typically adopted by designers in Reinforced Concrete (RC) solutions to cope with these tensile stresses. However, there is a growing interest in reinforcement solutions based on Fiber Reinforced Concrete (FRC). Within this framework, a broad experimental program was carried out to shed new lights on the behavior of Steel Fiber Reinforced Concrete (SFRC) specimens subjected to partially loaded area and to compare their structural performance against RC samples. Prismatic elements reinforced either by reinforcing bars or different steel fiber types and amount were subjected to a load applied over a partial area. Different casting directions, favoring different fiber orientations, were considered as well. The goal is to evaluate the crack control promoted by fibers and the different failure mechanisms of SFRC samples. Results confirmed both the ability of steel fibers to increase the splitting bearing capacity and the importance of fiber orientation. SFRC characterized by a proper post-cracking performance can move the collapse from splitting to crushing and provide a cracking control similar to RC specimens.